Analysis of Gender Based Reading Interest Index for High School Students at West Sumbawa Regency in 2021 - Rizka Donny Agung Saputra; Enida Fatmalia (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this study was to analyze the reading interest index, inhibiting factors and efforts to increase reading interest in high school students equivalent in West Sumbawa Regency. The research approach used exploratory descriptive and Field Research with survey methods. The population of this study consisted of 1,754 students spread over 21 schools, with the purposive sampling technique and the numbers were calculated using the Slovin formula, so the total sample was 325 students. The instruments used to collect research data were non-test instruments in the form of questionnaires, interviews and literature reviews. The research data were then analyzed by categorizing the reading interest index. The results showed that: 1) High school students equivalent in West Sumbawa district with Gender Women have a higher interest in reading than men, but the index of reading interest was still in the